Cross-Commodity News Transmission and Volatility Spillovers in the German Energy Markets - Rikard Green; Karl Larsson; Veronika Lunina; Birger Nilsson (Lund University, School of Economics and Management, Department of Economics, 2016)
This study investigates volatility spillovers to electric power from large exogenous shocks in the prices of gas, coal, and carbon emission allowances in the German energy market. Our sample ranges from 2008 to 2016 and covers periods of different market conditions. We use a general VAR-BEKK model and the volatility impulse response function methodology to analyze and evaluate the spillover effects. Special attention is paid to selecting an appropriate econometric volatility model. Our results show that the spillover effects often are of a significant magnitude and display considerable variation over time and across commodities. Coal and gas generate non-negligible spillovers during almost the entire sample period. Carbon has very little impact during the early and late parts of the sample, but generates significant, and highly variable, spillovers during the period from 2011 to the end of 2014.
Keywords: C32; C58; G10; Q41; 330; energy markets; time-varying volatility spillovers; volatility impulse response function; skew-Student asymmetric BEKK